PARTITIONING TYPES IN PRODUCT MODULARISATION. (May 2020) - Pakkanen, J.; Lehtonen, T.; Juuti, T.
Abstract: Alternative ways to divide the product into modules, partitioning types, have been identified. The research material consists of the modularisation exercise at the university. Students modularised LEGO wheel loaders for product configuration. We began to see certain basic principles for partitioning the product into modules. From these, we compiled a collection of partitioning types. Similarities between the identified partitioning types and the literature exists. Future research is concerned with whether identified partitioning types would also support modularisation in industrial projects.